(untitled) (Al-Academy, 2023)
The form of the body is an active and essential anchor in the history of the development of the individual in general, because of the diverse images it carries and rich contents, including what is subjective and objective for the individual himself, until it seemed to have an active and influential message despite the difference in his philosophy. We find it among Western and Arab philosophers and even in different religious philosophies, so that this is reflected in the experience of the theatrical and plastic artist, so that the body forms the basic material for his desire for renewal through research and exploration for everything related to the aesthetics of the body and its surroundings, so the current research was concerned with studying the aesthetic and artistic productions of the body in terms of And its employment by the director in the theatrical performance, so it contained four chapters: (The methodological framework) presenting the research problem that emerged in the following question: (How did the Iraqi director employ the actor’s body aesthetically in the theatrical performance? Then the researcher moved to the importance of research and the need for it, limits search .The second chapter: which represents the theoretical framework, it included two sections: (The first topic: the aesthetic concept of the body). (The second topic: the aesthetic work of the body in the artistic achievement).Then (the procedural frame) an analysis of its sample, the play (Remember, O Body), the work of director Muhammad Moayed. The research concluded with the researcher’s findings, conclusions, recommendations, proposals, and a list of sources.